2019
DOI: 10.1136/gutjnl-2018-316250
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota fermentation-NLRP3 axis shapes the impact of dietary fibres on intestinal inflammation

Abstract: ObjectiveDiets rich in fermentable fibres provide an array of health benefits; however, many patients with IBD report poor tolerance to fermentable fibre-rich foods. Intervention studies with dietary fibres in murine models of colonic inflammation have yielded conflicting results on whether fibres ameliorate or exacerbate IBD. Herein, we examined how replacing the insoluble fibre, cellulose, with the fermentable fibres, inulin or pectin, impacted murine colitis resulting from immune dysregulation via inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(141 citation statements)
references
References 54 publications
4
122
0
1
Order By: Relevance
“…Prebiotic fibres show many beneficial effects including amelioration of inflammation in the colon and SCFAs produced from the fibres by SCFA-producing gut microbiota contribute to the beneficial effects. Although SCFAs, especially butyrate, have been known the beneficial effect on colitis, a recent study showed that the negative effect of butyrate on colitis in animal study 40 . Fermentable fibres altered microbiota composition, which induced excess butyrate production resulted in exacerbation of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Prebiotic fibres show many beneficial effects including amelioration of inflammation in the colon and SCFAs produced from the fibres by SCFA-producing gut microbiota contribute to the beneficial effects. Although SCFAs, especially butyrate, have been known the beneficial effect on colitis, a recent study showed that the negative effect of butyrate on colitis in animal study 40 . Fermentable fibres altered microbiota composition, which induced excess butyrate production resulted in exacerbation of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Our group showed that amoxicillin‐induced dysbiosis promoted an immune imbalance, with an increased pro‐inflammatory profile in the caecum and the ovary, with upregulated IL‐1β cytokine gene expression and a decrease in IL‐10 expression in both organs even in the absence of bacterial translocation for other organs (Figure ). We evaluate the expression of both genes in the organs since when they are differentially expressed they represent or an important acute pro‐inflammatory cytokine (IL‐1β), that is associated with a variety of inflammatory pattern when gut microbiota is altered, 21 or IL‐10 as a classic anti‐inflammatory cytokine which is also related to balance the gut of inflammatory status 22 . Meijer et al, 2010, discussed that the changes in the ration of Firmicutes to Bacteroidetes directly affect the gut inflammatory status 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Much higher concentrations are commonly present in the colonic lumen (about 20 mM) (36,37) but the epithelium in health is shielded by its continuous adherent mucus layer (38) , moreover butyrate metabolism by surface epithelial cells adds to protection of the more sensitive stem cells at the crypt base (39) . The intriguing studies by Singh et al showing the pro-inflammatory effects of inulin and their mediation via butyrate (31) should prompt us to look again at the possible role of butyrate in ulcerative colitis. Roediger and colleagues reported several decades ago that faecal butyrate concentrations were raised (to 35 mM) in active ulcerative colitis compared with an average 14 mM in controls (40) .…”
Section: Colorectal Cancer (And Inflammatory Bowel Disease) As a Bactmentioning
confidence: 98%